Patient Perception of Type 2 DM About DM Management During the Covid-19 Pandemic at Majenang Health Center 1 - Fairuz Herdian Eka Widyanto; M Marsito; E Ernawati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background: In Indonesia, the number of diabetics continues to increase from 10.7 million people in 2019 to 19.5 million people in 2021. Indonesia is ranked fifth with the highest number of diabetics in the world. The increase un the number of people eith type- 2 diabetes is due to socio-economic, demographic, environmental and genetic factors. Objective: To find out the patient's perception of type 2 DM about dm management during the covid-19 pandemic. Method: The type of research used in this study is qualitatively descriptive with a phenomenological approach. The sampling process in this study was carried out by purposive sampling while the data retrieval process was done by interview method (indepth interview) and for the length of the interview on each participant which is between 30-45 minutes. Each participant in the study will only be interviewed once and will not be re-interviewed. In this study, data saturation occurred in 5th participants so that the number of samples in this study was as many as 5 people. Results: In this study, researchers identified 3 themes, namely (1) Perception of the relationship of DM with Covid (2) Physical activity of DM patients (3) Diet of DM patients during pandemic. Conclusion: Based on the results of the study researchers concluded that participants in this study partly know that DM is one of the causes of Covid-19, in addition they also know and understand the diet and physical activity carried out to maintain the stability of blood sugar levels during the Covid-19 pandemic. Recommendation: The next suggestion for researchers is it is hoped that researchers will be able to further identify more broadly related to the role of families in treating Covid- 19 comorbid patients by modifying other methods that have been used before.